The Influence of Leadership Style and Work Motivation on Employee Performance and its Impact on the Quality of Public Services - Arief Purwanto; Rafli Sandho Dwi Laksana; Rahayu Puji Suci (Trescode Green Organization, 2024)
This study aims to examine and determine the influence of leadership style on the quality of public services, both directly and mediated by employee performance. The analysis also seeks to determine whether the relationships between variables are significant or not and whether they have a positive or negative relationship with employee performance at the District Office and Village Office of Pasuruan City. Total sampling was chosen because the population is less than 100, where all individuals in the population, either individually or collectively, are given the same opportunity to be selected as members of the sample, totaling 74 respondents. The analysis techniques used are descriptive statistics and inferential statistical analysis. The research model employs structural equation modeling (SEM), with calculations using the PLS-SEM. The results show that the leadership style variable has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Leadership style has a positive and significant effect on service quality. Work motivation has a positive and significant effect on service quality. Employee performance has a positive and significant effect on service quality. Leadership style has a positive and significant effect in mediating the relationship between service quality and employee performance. Work motivation has a positive and significant effect in mediating the relationship between service quality and employee performance.